Lost Wages: The COVID-19 Cost of School Closures - George Psacharopoulos; Victoria Collis; Harry A. Patrinos; Emiliana Vegas (Institute of Labor Economics (IZA), 2020)
Social distancing requirements associated with COVID-19 have led to school closures. In April, 192 countries had closed all schools and universities, affecting more than 90 percent of the world's learners: over 1.5 billion children and young people. Closures are expected to reduce schooling and lead to future losses in earnings. Starting from the assumption that every additional year of schooling translates to 8 percent in future earnings, this paper estimates and confirms the loss in marginal future earnings on the basis of a four-month shutdown. We also estimated the losses by level of education. The findings show that the school closures reduce future earnings. It is also likely that students from low-income countries will be affected most, where the earning losses will be devastating. These estimates are conservative, assuming closures end after four months, with schools re-opening in the new academic year, and that school quality will not suffer.
Keywords: I26; I20; J24; 330; COVID-19; earnings; education